TRANSFORMATIONAL LEADERSHIP STYLE AND ITS INFLUENCE ON ORGANIZATIONAL COMMITMENT IN COMMERCIAL BANKS IN KENYA - Kimeto, Dr. Angela Cherotich; K'Aol, Professor, George (European Journal of Business and Strategic Management, 2018)
Purpose:The purpose of this study was to investigate transformational leadership style and its influence on organizational commitment in commercial banks in Kenya. Methodology: The study adopted the positivist research philosophy and descriptive correlational design. A sample of 150 was drawn from a population of 240 senior managers of the 40 commercial banks of Kenya using stratified random sampling technique. The tool used to collect data was questionnaire. Out of 150 questionnaires that were administered, 139 responses were received from the senior managers, giving a 93% response rate. Data was analyzed using inferential statistics such as Pearson correlations, Chi Square, ANOVA and multiple linear regression. Results : Multiple regression reslts indicated that all the four idependent variables (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) significantly predicted organizational commitment. Multiple linear regression results also revealed that organizational culture significantly predicted organizational commitment. Based on the regression analysis results, the null hypotheses were rejected. The study therefore, concluded that transformational leadership style had a significant influence on organizational commitment among the senior managers of the commercial banks in Kenya. The study also concluded that organizational culture significantly moderated the relationship between transformational leadership style and organizational commitment in commercial banks in Kenya. Unique contribution to theory, practice and policy: The study provides a unique contribution to the theory and practice of transformational leadership by extending its application in a new context in terms how idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration affect organizational commitment in commercial banks in Kenya. The study also provides unique contribution in terms of recommendations for policy development initiatives aimed at improving employee commitment and performance in the banking industry in Kenya